Fifth Five-Year Plan 1974-1979 Draft Proposals Part II - Statements - Planning Commission (Planning Commission, 1974)
Fifth Five Year Plan 1974-79 Union Territory of Pondicherry Small farmers and Agricultural laborers Area development Programme Warehousing and marketing and Storage, Community Development Cooperation and Panchayat Irrigation and Power Mineral Development Health and Family Planning Statistics, training and Administration
Union Territory of Pondicherry
Revenue, Finance & Planning Department Pondicherry
Keywords: Outlay and expenditure Summary; Outlay and expenditure Scheme wise; Outlays for backward areas; Programme wise outlay and expenditure; Physical Programme Targets and achievements; Outlay and expenditure Centrally sponsored schemes; Union Territory of Pondicherry; Agricultural education and research; Dairying and Milk Supply